Lannistumaton Matti Kurikan haaveet ja haaksirikot kolmella mantereella - Suodenjoki, Sami; Salmi-Niklander, Kirsti; Seppälä, Mikko-Olavi; Salmesvuori, Päivi; Rajavuori, Anna Lumi Maria; Pollari, Mikko (Suomalaisen Kirjallisuuden Seuran Toimituksia seri, 2022)
Matti Kurikka (1863-1915) is a multi-dimensional and controversial character in Finnish history. He was a playwright, a journalist, a socialist, and a theosophist, as well as a speaker for sexual emancipation and women's rights. Kurikka was born in Ingria, and his activities spanned not only Finland, but also Australia and North America, in both of which he led utopian communities. This biographical study explores Kurikka as a literary and political figure and a builder of utopias, whose life opens fascinating views on the societal and cultural currents of the late nineteenth and early twentieth centuries. The book critically re-evaluates earlier research on Kurikka and highlights forgotten phases of his life by using new source materials found in three continents. The sources include digitized newspapers and periodicals, Kurikka's plays and non-fictional books, oral history, and political cartoons.